PENGEMBANGAN BAHAN AJAR MENULIS ILMIAH BERBASIS KETERAMPILAN 4C DI PRODI PENDIDIKAN BAHASA INDONESIA UNIVERSITAS BILLFATH - Siti Aisah; Sukiman Sukiman (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Teaching materials are the most basic thing to help the implementation of learning objectives. Likewise with the Scientific Writing Techniques Course in the Indonesian Language Education Study Program, FKIP, Billfath University there are no special teaching materials provided by lecturers, this is the reason for this research. The aims of this study include how to develop 4C skills-based Scientific Writing teaching materials, and to determine the feasibility of using 4C skills-based Scientific Writing teaching materials. The development model used is ADDIE development. The stages are (1) analysis, (2) design, (3) planning, (4) implementation, and (5) evaluation. Data collection was carried out using a validation sheet. Data analysis techniques use qualitative analysis by describing. The results of the study stated that Scientific Writing teaching materials were suitable for use based on the results of the validation which contained aspects of: (1) the feasibility of the content of the material, (2) the feasibility of presentation, (3) the feasibility of language, and (4) the feasibility of graphics.